2017
DOI: 10.1371/journal.pone.0175099
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of suboptimal biologic therapy over time in patients with ulcerative colitis and Crohn's disease in the United States

Abstract: This study assessed the occurrence of indicators for suboptimal biologic therapy among ulcerative colitis (UC) and Crohn’s disease (CD) patients over time in the United States (US). Data from a large US claims database (2005–2013) were used to retrospectively identify patients with diagnosed with either UC or CD who were new biologic users. Indicators of suboptimal biologic therapy included: dose escalation during the maintenance phase, discontinuation of the initial biologic, switch to another biologic within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 35 publications
(37 reference statements)
3
47
3
Order By: Relevance
“…However, in several studies reporting discontinuation rates for both CD and UC populations, there appeared to be no consistent differences between the two indications. It is important to note that no formal statistical comparison was conducted in any of these studies . Also, in a study conducted by Desai et al, IBD type was not a significant predictor of discontinuation in univariate analysis.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…However, in several studies reporting discontinuation rates for both CD and UC populations, there appeared to be no consistent differences between the two indications. It is important to note that no formal statistical comparison was conducted in any of these studies . Also, in a study conducted by Desai et al, IBD type was not a significant predictor of discontinuation in univariate analysis.…”
Section: Resultsmentioning
confidence: 95%
“…Six studies reported on rates of switching to another biologic agent, but they varied greatly in terms of study methods and reported switch rates (Table ). The switch rate among all patients who initiated the index biologic ranged from 4.5% to 20% in most studies . Chen et al reported time to switching with biologics in IBD (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations